Cardiac resynchronization therapy guided by cardiac magnetic resonance imaging: A prospective, single-centre randomized study (CMR-CRT) - Kočková, Radka; Sedláček, Kamil; Wichterle, Dan; Šikula, Viktor; Tintěra, Jaroslav; Jansová, Helena; Pravečková, Alena; Langová, Renata; Krýže, Lukáš; El-Husseini, Wael; Segeťová, Markéta; Kautzner, Josef (International journal of cardiology, 2018)
BACKGROUND: Cardiac resynchronization therapy (CRT) improves symptoms of heart failure (HF), morbidity and mortality in selected population. The aim of the study was to investigate the impact of cardiac magnetic resonance (CMR)-guided left ventricular (LV) lead placement on clinical outcomes and LV reverse remodelling in CRT recipients. METHODS: Patients with CRT indication were randomized for CMR-guided (CMR group) or electrophysiologically guided (EP group) LV lead placement between 2011 and 2014. The target site in the CMR group was defined as the most delayed, scar-free, in the EP group as the site with the longest interval between the QRS onset and local electrogram. The primary endpoint was a combination of cardiovascular death or HF hospitalization. Secondary endpoints were New York Heart Association (NYHA) Class improvement ≥1, LV endsystolic diameter reduction >10%, B-type natriuretic peptide reduction by ≥30%. RESULTS: A total of 99 patients (47 in the CMR and 52 in the EP group) were enrolled. During a median follow-up of 47 months, primary composite endpoint occurred in 5 patients in the CMR group and 14 patients in the EP group (HR = 0.46; 95% CI: 0.16-1.32). Patients with left bundle branch block and NYHA Class >2 had better clinical outcome in the CMR group (HR = 0.09; 95% CI: 0.01-0.75). CONCLUSIONS: The use of CMR did not result in significant reduction of combined endpoint of cardiovascular death or HF hospitalization in the total study population. Significant clinical benefit from CMR-guided procedure was observed in a subgroup of optimum CRT candidates with advanced HF.
Keywords: Female; výsledek terapie; ženské pohlaví; Heart Failure; Target segment; Resynchronization therapy; Cardiac Resynchronization Therapy; lidé; srdeční selhání; magnetická rezonance kinematografická; Treatment Outcome; Magnetic resonance; následné studie; Magnetic Resonance Imaging, Cine; srdeční resynchronizační terapie; prospektivní studie; Follow-Up Studies; Male; Aged; Prospective Studies; Heart failure; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans